Detection of cell-type-specific risk-CpG sites in epigenome-wide association studies - Xiangyu Luo (Nature Portfolio, 2019)
Cellular heterogeneity is one of the major confounding factors in EWAS studies. Here the authors present a statistical method, HIgh REsolution (HIRE), which enables the detection of risk-CpG sites for individual cell types.